Sodium-ion battery hard carbon material, preparation method thereof and sodium-ion battery adopting hard material

The paper black liquid is prepared into a high-performance hard carbon negative electrode material through spray pyrolysis technology, which solves the problems of improving the performance of paper black liquid treatment and sodium ion battery materials, and achieves the high energy density and cycle stability of sodium ion batteries.

CN119674069AActive Publication Date: 2025-03-21DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411873179.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize lignin and hemicellulose in papermaking black liquor to prepare high-performance sodium ion battery hard carbon materials, while solving the problem of papermaking black liquor treatment.

Method used

The black liquid of papermaking is atomized by spray pyrolysis technology and pyrolyzed at high temperature. A composite porous material embedded with hollow porous spheres and porous carbon sheets is prepared as hard carbon anode material, and the microstructure and electrochemical properties of the material are regulated through two sections of heat treatment.

Benefits of technology

The high-value utilization of papermaking black liquid is realized, and high-performance hard carbon negative electrode materials are prepared, which improves the energy density and cycle stability of sodium ion batteries, and the energy density reaches 160-180Wh/kg.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674069A_ABST
    Figure CN119674069A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery hard carbon material, a preparation method thereof and a sodium ion battery adopting the hard material. The hard carbon material is a composite porous material formed by embedding hollow porous balls and porous carbon plates. Compared with the prior art, the method has the advantages that spray pyrolysis is adopted to prepare the sodium ion hard carbon material from concentrated papermaking black liquid in a short process, and a precursor material with a hollow porous spherical structure is constructed through spray pyrolysis; collecting a precursor material by using an aqueous solution, and performing solid-liquid separation and washing to realize impurity removal; the microstructure of the carbon material is further regulated and controlled through two-stage heat treatment, and the hard carbon negative electrode material with high specific capacity and excellent rate capability and cycling stability is obtained. The high-energy-density sodium ion battery is prepared by taking the hard carbon material as a negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ions and battery materials thereof, and in particular to a sodium ion battery hard carbon material and a preparation method thereof, and a sodium ion battery using the hard material. Background Art

[0002] Sodium-ion batteries are green and environmentally friendly batteries with the closest electrical properties to lithium-ion batteries. In addition to having the characteristics of high operating voltage, high specific energy and long cycle life, they also have the advantages of abundant resources, good low-temperature performance, over-discharge resistance and low cost. They have great potential in large-scale energy storage and have developed rapidly in recent years. Hard carbon negative electrode materials are the key materials of sodium-ion batteries. Their microstructure and morphology, pore structure and pore size distribution significantly affect their performance. Common precursors for preparing hard carbon materials include biomass, synthetic polymers and fossil fuels.

[0003] Lignin is a natural macromolecular organic compound with abundant resources, second only to cellulose in content in the plant kingdom. It has a unique and complex aromatic and aliphatic main chain structure and functional groups suitable for functionalization. After treatment, it can become an important chemical raw material and energy material. Papermaking black liquor is a dark brown wastewater containing a large amount of lignin produced by the alkaline pulping process. It also contains some hemicellulose, residual alkali, etc. Black liquor concentrates almost 90% of the pollutants discharged from papermaking. Direct discharge into water bodies will cause serious pollution.

[0004] Spray pyrolysis is a new technology for preparing solid particulate materials in a short process, in which a solution is atomized into tiny droplets through a spray device, and the droplets are rapidly evaporated and the solute is thermally decomposed under high temperature.

[0005] This project aims to efficiently utilize high-molecular organic matter such as lignin and hemicellulose in papermaking black liquor, directly prepare high-performance hard carbon negative electrode materials through spray pyrolysis, realize short-process and high-value application of papermaking black liquor, and use the hard carbon material as the negative electrode to prepare high-energy density sodium-ion batteries. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a sodium ion battery hard carbon material and a preparation method thereof, and a sodium ion battery using the hard material, in response to the above-mentioned technical summary of the problems of sodium ion battery hard carbon material and papermaking black liquor treatment.

[0007] In order to solve the above technical problems, the technical solution provided by the present invention is: a hard carbon material for sodium ion battery, wherein the hard carbon material is a composite porous material inlaid with hollow porous balls and porous carbon sheets, wherein the diameter of the hard carbon microspheres is about 0.3-3um, the wall thickness is about 30-100nm, and the (002) crystal plane interlayer spacing (d 002 ) is 0.36-0.38nm, and the average thickness along the c-axis direction (Lc ) is 0.6-0.75nm, and the average width along the a-axis direction (L a ) is 11-14nm.

[0008] The method for preparing a sodium ion battery hard carbon material is to obtain a sodium ion hard carbon negative electrode material by spray pyrolysis and high temperature heat treatment of papermaking black liquor. The specific steps include:

[0009] Step 1: Preparation of precursor materials by spray pyrolysis. The papermaking black liquor is atomized, and an inert gas is used as a carrier gas. The atomized droplets and the inert gas enter the atmosphere protection furnace together, and high-temperature pyrolysis is performed in the atmosphere protection furnace. After the spray pyrolysis is completed, the collected carbon material is washed and dried to obtain the precursor material.

[0010] Step 2: High-temperature heat treatment to regulate composition and microstructure. The precursor material prepared above is placed in a protective atmosphere furnace for high-temperature heat treatment, and then cooled to obtain a hard carbon negative electrode material.

[0011] As an improvement, the total dissolved solids (including lignin, hemicellulose and their derivatives, sodium salts, residual alkali, etc.) in the papermaking black liquor is 50-600 g / L, the total carbon content (TOC) is 10-100 g / L, and the hydroxide (OH - ) content is 2-30g / L, and the sodium (Na) content is 10-100g / L.

[0012] As an improvement, the precursor material has a spherical porous structure, and some carbon spheres are collapsed, which is a porous spherical material rich in mesoporous structure.

[0013] As an improvement, the water partial pressure in the atmosphere protection furnace in step 1 is 0.1-0.5atm.

[0014] As an improvement, in the step 1, the temperature of the papermaking black liquor during atomization is 40-70°C, the atomization methods include ultrasonic atomization and centrifugal atomization, and the high-temperature pyrolysis temperature is 550-750°C.

[0015] As an improvement, the high temperature heat treatment in step 2 includes two stages of heat treatment, namely, firstly heating to 450-600°C at 5-20°C / min and keeping the temperature constant for 1-12h, and then heating to 1300-1600°C at 1-5°C / min and keeping the temperature constant for 1-12h.

[0016] As an improvement, preferably, one or more of polyaziridine, ethylenediamine, and diethylenetriamine are added to the papermaking black liquor in step 1. A nitrogen-doped spherical porous structure precursor material and a composite porous material inlaid with nitrogen-doped hollow porous spheres and porous carbon sheets are prepared. The proportion of N atoms in the precursor and the hard carbon material is 0.1 to 0.5 wt%.

[0017] A sodium ion battery using hard carbon material, using the hard carbon material as a negative electrode material, using a high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide as a positive electrode material, an electrolyte of 1-1.3 mol / LNaPF6 propylene carbonate (PC) / ethyl methyl carbonate (EMC) (volume ratio of x:1-x, where x=0.15-0.35) solution, and adding 0.5%-3% of propylene sulfite (PS) and 1%-5% of fluoroethylene carbonate (FEC) additives, to prepare a high-voltage soft-pack sodium ion battery that can be charged and discharged between 1.5V and 4.15V, with an energy density of 160-180Wh / kg.

[0018] After adopting the above structure, the present invention has the following advantages:

[0019] (1) Spray pyrolysis is used to prepare sodium ion hard carbon materials from concentrated papermaking black liquor in a short process, which can be used as negative electrode materials for sodium ion batteries, thus realizing the short-process high-value utilization of papermaking black liquor.

[0020] (2) Using spray pyrolysis to construct a precursor material with a hollow porous spherical structure. The resulting precursor has a spherical porous structure, and some carbon spheres are collapsed, which is a porous spherical material rich in mesoporous structure.

[0021] (3) The solid material and tail gas after pyrolysis are introduced into a collector containing a dilute sodium hydroxide solution, thereby achieving the purposes of sealing the atmosphere protection furnace, collecting the porous carbon material, absorbing and treating the pyrolysis tail gas, and removing soluble impurities.

[0022] (4) The hollow porous spherical structure precursor material is further regulated by two-stage heat treatment. The low-temperature heat treatment makes the pyrolysis of the precursor material more complete and stabilizes the morphology and pore structure of the precursor material. The high-temperature heat treatment further regulates the crystal structure and functional groups of the material to obtain a high-performance hard carbon negative electrode material.

[0023] (5) In combination with the characteristics of the reaction system, nitrogen-containing compounds such as poly(aziridine), ethylenediamine, and diethylenetriamine were added to the papermaking black liquor to obtain spherical porous structure precursor materials with uniform in-situ nitrogen distribution at the molecular level and composite porous materials inlaid with nitrogen-doped hollow porous spheres and porous carbon sheets, which significantly improved the electrochemical properties of hard carbon materials.

[0024] (6) The hard carbon material of the present invention is used as the negative electrode material, the high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material, the electrolyte is a PC / EMC solution of NaPF6 and PS and FEC additives are added, and the prepared high-voltage soft-pack sodium ion battery has a high energy density (160-180Wh / kg). BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a SEM image of the pyrolyzed hard carbon material of the present invention;

[0026] Figure 2 is a SEM image of the pyrolyzed hard carbon material of the present invention;

[0027] Figure 3 is a TEM image of the pyrolyzed hard carbon material of the present invention;

[0028] Figure 4 is a TEM image of the pyrolyzed hard carbon material of the present invention;

[0029] Figure 5 It is a charge and discharge curve diagram of the sodium ion battery using pyrolysis hard carbon material of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0031] Combined with Figure 1-5 A hard carbon material for sodium ion battery, wherein the hard carbon material is a composite porous material inlaid with hollow porous spheres and porous carbon sheets, wherein the diameter of the hard carbon microspheres is about 0.3-3 μm, the wall thickness is about 30-100 nm, and the (002) crystal plane interlayer spacing (d 002 ) is 0.36-0.38nm, and the average thickness along the c-axis direction (L c ) is 0.6-0.75nm, and the average width along the a-axis direction (L a ) is 11-14nm.

[0032] The sodium ion hard carbon negative electrode material is obtained by spray pyrolysis and high temperature heat treatment of papermaking black liquor, and the specific steps include:

[0033] Step 1: Preparation of precursor materials by spray pyrolysis. The papermaking black liquor is atomized, and an inert gas is used as a carrier gas. The atomized droplets and the inert gas enter the atmosphere protection furnace together, and are pyrolyzed at high temperature in the atmosphere protection furnace. After the spray pyrolysis is completed, the collected carbon material is washed and dried to obtain the precursor material;

[0034] Step 2: High-temperature heat treatment to regulate composition and microstructure. The precursor material prepared above is placed in a protective atmosphere furnace for high-temperature heat treatment, and then cooled to obtain a hard carbon negative electrode material.

[0035] The total dissolved solids (including lignin, hemicellulose and their derivatives, sodium salt, residual alkali, etc.) in the papermaking black liquor are 50-600 g / L, the total carbon content (TOC) is 10-100 g / L, and the hydroxide (OH) -) content is 2-30g / L, sodium (Na) content is 10-100g / L, the precursor material has a spherical porous structure, some carbon balls are collapsed, and it is a porous spherical material rich in mesoporous structure. The water partial pressure in the atmosphere protection furnace in the step one is 0.1-0.5atm. When the papermaking black liquor is atomized in the step one, the temperature of the papermaking black liquor is 40-70℃, the atomization method includes ultrasonic atomization and centrifugal atomization, and the high-temperature pyrolysis temperature is 550-750℃. The high-temperature heat treatment in the step two includes two-stage heat treatment, that is, first heating to 450-600℃ at 5-20℃ / min, keeping the temperature constant for 1-12h, and then heating to 1300-1600℃ at 1-5℃ / min, and keeping the temperature constant for 1-12h. Preferably, in the step one, one or more of polyaziridine, ethylenediamine and diethylenetriamine are added to the papermaking black liquor. A nitrogen-doped spherical porous structure precursor material and a composite porous material inlaid with nitrogen-doped hollow porous spheres and porous carbon sheets are prepared. The proportion of N atoms in the precursor and the hard carbon material is 0.1-0.5wt%.

[0036] The hard carbon material is used as the negative electrode material, a high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material, the electrolyte is 1-1.3 mol / LNaPF6 propylene carbonate (PC) / ethyl methyl carbonate (EMC) (volume ratio is x:1-x, where x=0.15-0.35) solution, and 0.5%-3% propylene sulfite (PS) and 1%-5% fluoroethylene carbonate (FEC) additives are added to prepare a high-voltage soft-pack sodium ion battery that can be charged and discharged between 1.5V and 4.15V, and the energy density is 160-180Wh / kg.

[0037] Specific Example 1: Preparation of Hollow Porous Spheres by Spray Pyrolysis Precursor: Papermaking Black Liquor (Total Dissolved Solids 60 g / L, TOC 10 g / L, OH - 5g / L, Na10g / L) were heated to 40℃ and then ultrasonically atomized. Nitrogen was used as the carrier gas. The atomized droplets entered the atmosphere protection furnace together with nitrogen (3L / min). H2O =0.4atm) at 700°C for high temperature pyrolysis, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, it is filtered, washed and dried to obtain a precursor material.

[0038] High-temperature heat treatment to regulate the microstructure: The porous spherical precursor material prepared above was placed in a nitrogen protective atmosphere furnace, first heated to 500°C at 10°C / min, kept constant at this temperature for 2h, then heated to 1400°C at 5°C / min, kept constant at this temperature for 2h, and then cooled with the furnace to obtain a hard carbon negative electrode material inlaid with hollow porous spheres and porous carbon sheets.

[0039] The obtained hard carbon material is a composite porous material inlaid with hollow porous spheres and porous carbon sheets. The diameter of the hard carbon microspheres is about 0.3-2um, the wall thickness is about 30-100nm, and the interlayer spacing d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.72nm. a The obtained hard carbon negative electrode material was used as an active material to make an electrode, which was assembled into a button battery with a metal lithium sheet, a separator, and an electrolyte. The battery was charged and discharged at a current density of 0.1C (30mA / g) between 0-1.5V, and the reversible capacity was 342mAh / g. After 300 cycles at 0.5C (150mA / g), the capacity retention rate was 97.5%.

[0040] The hard carbon material prepared in this embodiment is used as the negative electrode material, and the high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material. The electrolyte is 1 mol / LNaPF6 PC / EMC (volume ratio is x:1-x, where x=0.3) solution and 1% PS and 3% FEC additives are added. The prepared soft-pack sodium ion battery is charged and discharged between 1.5V-4.15V, and the energy density is 165Wh / kg.

[0041] Specific Example 2: Preparation of Hollow Porous Spheres by Spray Pyrolysis Precursor: Papermaking Black Liquor (Total Dissolved Solids 120 g / L, TOC 21 g / L, OH - 5.5g / L, Na20g / L) was heated to 50℃ and then ultrasonically atomized. Nitrogen was used as the carrier gas. The atomized droplets and nitrogen (5L / min) entered the atmosphere protection furnace together. H2O =0.2atm) and subjected to high temperature pyrolysis at 550°C. The obtained carbon material and tail gas are introduced into a collector containing a dilute sodium hydroxide solution. After the spray pyrolysis is completed, the precursor material is filtered, washed and dried.

[0042] High-temperature heat treatment to regulate the microstructure: The porous spherical precursor material prepared above was placed in a nitrogen-protected atmosphere furnace, first heated to 450°C at 20°C / min, kept constant at this temperature for 12 hours, then heated to 1300°C at 5°C / min, kept constant at this temperature for 12 hours, and then cooled with the furnace to obtain a hard carbon negative electrode material inlaid with hollow porous spheres and porous carbon sheets.

[0043] The obtained hard carbon material is a composite porous material inlaid with hollow porous spheres and porous carbon sheets. The diameter of the phenolic resin-based hard carbon microspheres is about 0.3-3um, the wall thickness is about 30-100nm, and the interlayer spacing d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.61 nm.a The obtained hard carbon negative electrode material was used as an active material to make an electrode, which was assembled into a button battery with a metal lithium sheet, a separator, and an electrolyte. The battery was charged and discharged at a current density of 0.1C (30mA / g) between 0-1.5V, and the reversible capacity was 342mAh / g. After 300 cycles at 0.5C (150mA / g), the capacity retention rate was 98.1%.

[0044] The hard carbon material prepared in this embodiment is used as the negative electrode material, and the high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material. The electrolyte is 1.3 mol / LNaPF6 PC / EMC (volume ratio is x:1-x, where x=0.35) solution and 0.5% PS and 5% FEC additives are added. The prepared soft-pack sodium ion battery is charged and discharged between 1.5V-4.15V, and the energy density is 162Wh / kg.

[0045] Specific Example 3: Preparation of Hollow Porous Spheres by Spray Pyrolysis Precursor: Papermaking Black Liquor (Total Dissolved Solids 595 g / L, TOC 98 g / L, OH - 29g / L, Na98g / L) were heated to 65℃ and centrifugally atomized. Nitrogen was used as carrier gas. The atomized droplets and nitrogen (10L / min) entered the atmosphere protection furnace together. H2O =0.1atm) at 750°C for high temperature pyrolysis, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, it is filtered, washed and dried to obtain a precursor material.

[0046] High-temperature heat treatment to regulate the microstructure: The porous spherical precursor material prepared above was placed in a nitrogen-protected atmosphere furnace, first heated to 500°C at 20°C / min, kept constant at this temperature for 2 hours, then heated to 1400°C at 1°C / min, kept constant at this temperature for 2 hours, and then cooled with the furnace to obtain a hard carbon negative electrode material inlaid with hollow porous spheres and porous carbon sheets.

[0047] The obtained hard carbon material is a composite porous material inlaid with hollow porous spheres and porous carbon sheets. The diameter of the hard carbon microspheres is about 0.5-3um, the wall thickness is about 30-100nm, and the interlayer spacing d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.75 nm. a The obtained hard carbon negative electrode material was used as an active material to make an electrode, which was assembled into a button battery with a metal lithium sheet, a separator, and an electrolyte. The battery was charged and discharged at a current density of 0.1C (30mA / g) between 0-1.5V, and the reversible capacity was 348mAh / g. After 300 cycles at 0.5C (150mA / g), the capacity retention rate was 98.0%.

[0048] The hard carbon material prepared in this embodiment is used as the negative electrode material, and the high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material. The electrolyte is 1.2 mol / LNaPF6 PC / EMC (volume ratio is x:1-x, where x=0.15) solution and 3% PS and 1% FEC additives are added. The prepared soft-pack sodium ion battery is charged and discharged between 1.5V-4.15V, and the energy density is 167Wh / kg.

[0049] Specific Example 4: Preparation of Hollow Porous Ball Precursor by Spray Pyrolysis: In papermaking black liquor (total dissolved solids 120 g / L, TOC 21 g / L, OH - 5.5g / L, Na20g / L) was added with 2% polyaziridine, heated to 70°C and then ultrasonically atomized, with nitrogen as the carrier gas. The atomized droplets and nitrogen (3L / min) were introduced into the atmosphere protection furnace. H2O =0.4atm) at 650°C for high temperature pyrolysis, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, it is filtered, washed and dried to obtain a nitrogen-doped precursor material.

[0050] High-temperature heat treatment to regulate the microstructure: The porous spherical precursor material prepared above was placed in a nitrogen-protected atmosphere furnace, first heated to 500°C at 20°C / min, kept constant at this temperature for 3 hours, then heated to 1400°C at 2°C / min, kept constant at this temperature for 2 hours, and then cooled with the furnace to obtain a nitrogen-doped hard carbon negative electrode material inlaid with hollow porous spheres and porous carbon sheets.

[0051] The obtained hard carbon material is a composite porous material inlaid with hollow porous spheres and porous carbon sheets. The diameter of the hard carbon microspheres is about 0.3-3um, the wall thickness is about 30-100nm, and the interlayer spacing d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.71 nm. a The obtained hard carbon negative electrode material was used as an active material to make an electrode, which was assembled into a button battery with a metal lithium sheet, a separator, and an electrolyte. The battery was charged and discharged at a current density of 0.1C (30mA / g) between 0-1.5V, and the reversible capacity was 380mAh / g. After 300 cycles at 0.5C (150mA / g), the capacity retention rate was 97.6%.

[0052] The hard carbon material prepared in this embodiment is used as the negative electrode material, and the high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material. The electrolyte is 1.1 mol / LNaPF6 PC / EMC (volume ratio is x:1-x, where x=0.25) solution and 1.5% PS and 2% FEC additives are added. The prepared soft-pack sodium ion battery is charged and discharged between 1.5V-4.15V, and the energy density is 180Wh / kg.

[0053] Specific Example 5: Preparation of Hollow Porous Ball Precursor by Spray Pyrolysis: In papermaking black liquor (total dissolved solids 60 g / L, TOC 10 g / L, OH - 5g / L, Na10g / L) was added with 5% ethylenediamine, heated to 40°C and then ultrasonically atomized, with nitrogen as the carrier gas. The atomized droplets and nitrogen (3L / min) were introduced into the atmosphere protection furnace. H2O =0.4atm) at 650°C for high temperature pyrolysis, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, it is filtered, washed and dried to obtain a nitrogen-doped precursor material.

[0054] High-temperature heat treatment to regulate the microstructure: The porous spherical precursor material prepared above was placed in a nitrogen-protected atmosphere furnace, first heated to 600°C at 20°C / min, kept constant at this temperature for 3 hours, then heated to 1400°C at 2°C / min, kept constant at this temperature for 2 hours, and then cooled with the furnace to obtain a nitrogen-doped hard carbon negative electrode material inlaid with hollow porous spheres and porous carbon sheets.

[0055] The obtained hard carbon material is a composite porous material inlaid with hollow porous spheres and porous carbon sheets. The diameter of the hard carbon microspheres is about 0.3-3um, the wall thickness is about 30-100nm, and the interlayer spacing d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.69 nm. a The obtained hard carbon negative electrode material was used as an active material to make an electrode, which was assembled into a button battery with a metal lithium sheet, a separator, and an electrolyte. The battery was charged and discharged at a current density of 0.1C (30mA / g) between 0-1.5V, and the reversible capacity was 370mAh / g. After 300 cycles at 0.5C (150mA / g), the capacity retention rate was 97.8%.

[0056] The hard carbon material prepared in this embodiment is used as the negative electrode material, and the high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material. The electrolyte is 1.2 mol / LNaPF6 PC / EMC (volume ratio is x:1-x, where x=0.25) solution and 1.5% PS and 2% FEC additives are added. The prepared soft-pack sodium ion battery is charged and discharged between 1.5V-4.15V, and the energy density is 172Wh / kg.

[0057] Specific Example 6: Preparation of hollow porous sphere precursor by spray pyrolysis: In papermaking black liquor (total dissolved solids 60g / L, TOC 10g / L, OH - 5g / L, Na10g / L) was added with 5% diethylenetriamine, heated to 50℃ and then ultrasonically atomized, with nitrogen as carrier gas, the atomized droplets and nitrogen (3L / min) were introduced into the atmosphere protection furnace. H2O =0.4atm) at 650°C for high temperature pyrolysis, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, it is filtered, washed and dried to obtain a nitrogen-doped precursor material.

[0058] High-temperature heat treatment to regulate the microstructure: The porous spherical precursor material prepared above was placed in a nitrogen-protected atmosphere furnace, first heated to 500°C at 20°C / min, kept constant at this temperature for 3 hours, then heated to 1400°C at 2°C / min, kept constant at this temperature for 2 hours, and then cooled with the furnace to obtain a nitrogen-doped hard carbon negative electrode material inlaid with hollow porous spheres and porous carbon sheets.

[0059] The obtained hard carbon material is a composite porous material inlaid with hollow porous spheres and porous carbon sheets. The diameter of the hard carbon microspheres is about 0.3-3um, the wall thickness is about 30-100nm, and the interlayer spacing d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.71 nm. a The obtained hard carbon negative electrode material was used as an active material to make an electrode, which was assembled into a button battery with a metal lithium sheet, a separator, and an electrolyte. The battery was charged and discharged at a current density of 0.1C (30mA / g) between 0-1.5V, and the reversible capacity was 375mAh / g. After 300 cycles at 0.5C (150mA / g), the capacity retention rate was 97.7%.

[0060] The hard carbon material prepared in this embodiment is used as the negative electrode material, and the high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material. The electrolyte is 1.1 mol / LNaPF6 PC / EMC (volume ratio is x:1-x, where x=0.25) solution and 1.5% PS and 2% FEC additives are added. The prepared soft-pack sodium ion battery is charged and discharged between 1.5V-4.15V, and the energy density is 174Wh / kg.

[0061] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual structure is not limited thereto. In short, if a person skilled in the art is inspired by it, and does not deviate from the purpose of the invention, and does not creatively design a structure and implementation method similar to the technical solution, they should all fall within the protection scope of the present invention.

Claims

1. A sodium ion battery hard carbon material, characterized in that: The hard carbon material is a composite porous material in which hollow porous balls and porous carbon sheets are inlaid. The diameter of the hard carbon microspheres is about 0.3-3 μm, the wall thickness is about 30-100 nm, and the (002) crystal plane interlayer spacing (d 002 ) is 0.36-0.38nm, and the average thickness along the c-axis direction (L c ) is 0.6-0.75nm, and the average width along the a-axis direction (L a ) is 11-14nm.

2. The method for preparing a sodium ion battery hard carbon material according to claim 1, characterized in that: The sodium ion hard carbon negative electrode material is obtained by spray pyrolysis and high temperature heat treatment of papermaking black liquor, and the specific steps include: Step 1: Prepare the precursor material by spray pyrolysis. The papermaking black liquor is atomized, and an inert gas is used as a carrier gas. The atomized droplets and the inert gas enter the atmosphere protection furnace together, and high-temperature pyrolysis is performed in the atmosphere protection furnace. After the spray pyrolysis is completed, the collected carbon material is washed and dried to obtain the precursor material; Step 2: High-temperature heat treatment to regulate the composition and microstructure. The precursor material prepared above is placed in a protective atmosphere furnace for high-temperature heat treatment, and then cooled to obtain a hard carbon negative electrode material.

3. The method for preparing a sodium ion battery hard carbon material according to claim 2, characterized in that: The total dissolved solids (including lignin, hemicellulose and their derivatives, sodium salt, residual alkali, etc.) in the papermaking black liquor are 50-600 g / L, the total carbon content (TOC) is 10-100 g / L, and the hydroxide (OH) - ) content is 2-30g / L, and the sodium (Na) content is 10-100g / L.

4. The method for preparing a sodium ion battery hard carbon material according to claim 2, characterized in that: The precursor material has a spherical porous structure, and some carbon balls are collapsed, which is a porous spherical material rich in mesoporous structure.

5. The method for preparing a sodium ion battery hard carbon material according to claim 2, characterized in that: In the step 1, the water partial pressure in the atmosphere protection furnace is 0.1-0.5 atm.

6. The method for preparing a sodium ion battery hard carbon material according to claim 2, characterized in that: In the step 1, the temperature of the papermaking black liquor during atomization is 40-70° C., the atomization method includes ultrasonic atomization and centrifugal atomization, and the high-temperature pyrolysis temperature is 550-750° C.

7. The method for preparing a sodium ion battery hard carbon material according to claim 2, characterized in that: The high temperature heat treatment in step 2 includes two stages of heat treatment, namely, firstly heating to 450-600°C at 5-20°C / min and keeping the temperature constant for 1-12h, and then heating to 1300-1600°C at 1-5°C / min and keeping the temperature constant for 1-12h.

8. The method for preparing a sodium ion battery hard carbon material according to claim 2, characterized in that: Preferably, in step one, one or more of polyaziridine, ethylenediamine, and diethylenetriamine are added to the papermaking black liquor to prepare a nitrogen-doped spherical porous structure precursor material and a composite porous material inlaid with nitrogen-doped hollow porous spheres and porous carbon sheets, and the proportion of N atoms in the precursor and the hard carbon material is 0.1 to 0.5 wt%.

9. A sodium ion battery using the hard carbon material of claim 1, characterized in that: The hard carbon material as claimed in claim 1 is used as the negative electrode material, and a high-voltage layered sodium-nickel-iron-manganese-copper-titanium composite oxide is used as the positive electrode material. The electrolyte is a 1-1.3 mol / LNaPF6 solution of propylene carbonate (PC) / ethyl methyl carbonate (EMC) (volume ratio is x:1-x, where x=0.15-0.35) and 0.5%-3% of propylene sulfite (PS) and 1%-5% of fluoroethylene carbonate (FEC) additives are added to prepare a high-voltage soft-pack sodium ion battery that can be charged and discharged between 1.5V-4.15V, and the energy density is 160-180Wh / kg.

Citation Information

Patent Citations

  • Hard carbon microspheres with adjustable morphology and pore structure, and preparation method and application thereof

    CN110921647A

  • Graphene-based composite hollow carbon sphere material and preparation method thereof

    CN116621161A